Fragrance transfer between fabrics for forensic reconstruction applications. Issue 3 (May 2019) - Gherghel, Simona; Morgan, Ruth M.; Arrebola-Liébanas, Javier F.; Blackman, Chris S.; Parkin, Ivan P.
Abstract: Sexual assault is a serious crime that often has low conviction rates. Recent literature has demonstrated that there is potential for fragrances to be valuable in forensic reconstructions where there has been contact between individuals. However, developing appropriate evidence bases for understanding the nature of fragrance transfer in these contexts is needed. This article presents three experiments that address the transfer process of fragrances that have been transferred from a primary piece of fabric onto a secondary piece of fabric, in a manner that could occur during an assault. The three variables studied were the ageing time of the fragrances on the first fabric prior to transfer, the contact time between the two fabrics, and lastly the fabric type (of the primary material and the recipient material). The transfer was evaluated using a validated solid phase micro-extraction gas chromatography–mass spectrometry (SPME GC–MS) method. The findings demonstrated that all three variables had an impact on the transfer of fragrances between clothing fabrics. Generally, lower volatility compounds were transferred and recovered in larger amounts than higher volatility compounds. All fragrance compounds were successfully recovered from a secondary piece of fabric even when the contact time was as short as 10 s, and even when the perfume was aged on the primary fabric for as long as 48 h. The nature of the fragrance transfer also depended on the fabric type, so that a clear discrimination was observed between the fragrance transfer that occurred onto a natural fabric (cotton) and onto a synthetic fabric (polyester). Highlights: Fragrance traces were recovered from a recipient fabric for contacts as short as 10 s. Fragrance traces were recovered from a recipient fabric for ageing times of up to 48 h. Differences were identified between fragrance transfer to cotton and polyester. Fragrance is a form of trace evidence that shows potential for forensic reconstructions.